Postpartum Contraception: A Neglected Field to Avoid Unplanned Pregnancy and Short Inter-Pregnancy Intervals: Postpartum Contraception: Unplanned Pregnancy and Short Inter-Pregnancy Intervals - Shoaib, Momina; Gul, Fouzia; Mehsud, Razia; Maqsood, Laila; Firdous, Samina; Tariq, Maryam (Pakistan Journal of Health Sciences, 2025)
Postpartum contraception plays a crucial role in preventing unintended pregnancies and optimizing birth spacing. However, its utilization remains suboptimal in many low- and middle-income settings. Objectives: To determine the prevalence, method mix, and factors associated with postpartum contraceptive use among women attending KMU-IMS, Kohat. Methods: A cross-sectional study was conducted among 103 postpartum women attending the Department of Obstetrics and Gynecology, Khyber Medical University Institute of Medical Sciences and Liaqat Memorial Hospital, Kohat. Data were collected using a structured questionnaire and analyzed using SPSS version 25.0. Descriptive statistics summarized demographic and clinical characteristics, while Chi-square and Fisher’s exact tests examined bivariate associations. Variables with p<0.2 were included in multivariable logistic regression to identify independent predictors. Results: The prevalence of postpartum contraceptive use was 47.6%. The most commonly used methods were the lactational amenorrhea method (28.6%), condoms (22.4%), and oral contraceptive pills (14.3%). Most women (38.8%) initiated contraception within six weeks postpartum. No significant associations were found between contraceptive use and socio-demographic or obstetric variables. Women with vaginal deliveries reported higher use (57.9%) than those with caesarean (35.0%) or assisted deliveries (33.3%) (Fisher’s p=0.071). After adjusting for confounders, none of the factors remained statistically significant; caesarean delivery showed higher but non-significant odds (aOR = 2.69, 95% CI 1.03–7.00, p=0.043). Conclusion: Postpartum contraceptive use among women attending KMU-IMS, Kohat, was moderate, with a preference for temporary methods. Utilization appeared independent of most socio-demographic and obstetric factors, underscoring the need to strengthen postnatal counseling and address individual and cultural barriers to improve uptake.